L'engagement et la persistance dans les dispositifs de formation en ligne : regards croisés - Gaëlle Molinari; Bruno Poellhuber; Jean Heutte; Elise Lavoué; Denise Sutter Widmer; Pierre-André Caron (Centre National d'Enseignement à Distance, 2016)
The authors describe the theoretical and methodological approaches they use in their research when studying the phenomena of engagement and persistence in distance learning settings. This paper is organized into three sections corresponding to three different perspectives on engagement: a section about student engagement in distance learning and MOOCs; a section about engagement in serious game; and a section about engagement in learning communities and in computer-supported (distance) collaborative learning. Each section provides a definition of engagement, identifies factors of engagement and describes existing measures of engagement. This paper ends with a synthesis of theses perspectives and opens up with new research questions.